2012
DOI: 10.1007/s10152-012-0334-z
|View full text |Cite
|
Sign up to set email alerts
|

Benthos and demersal fish habitats in the German Exclusive Economic Zone (EEZ) of the North Sea

Abstract: We compiled data from different monitoring surveys to analyse and compare community and diversity patterns of fish, epi-and infauna in the German Exclusive Economic Zone (EEZ) of the North Sea in order to identify benthic habitats common to all faunal components. We found congruent community patterns of fish, epi-and infauna for the coastal waters, the Oysterground and the area called ''Duck's Bill'', which coincided with specific abiotic characteristics of these regions. The three regions were defined as spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Most of the community‐weighted mean trait values changed with depth and physical oceanographic variables, indicating that environmental filtering was occurring. This result is common in studies at large spatial scales, where faunal zonation is aligned to the different hydrographic regimes (Neumann et al, ). Depth and maximum bottom current speed were the best environmental predictors, contributing 38.9% and 14.7% of the total explained variation, whereas interspecific interactions as inferred from the random effect at the sample level, and which can also account for missing environmental covariates (Zurrell, Pollock, & Thuiller, ), accounted for 16.3% of the variance in the model.…”
Section: Discussionmentioning
confidence: 57%
“…Most of the community‐weighted mean trait values changed with depth and physical oceanographic variables, indicating that environmental filtering was occurring. This result is common in studies at large spatial scales, where faunal zonation is aligned to the different hydrographic regimes (Neumann et al, ). Depth and maximum bottom current speed were the best environmental predictors, contributing 38.9% and 14.7% of the total explained variation, whereas interspecific interactions as inferred from the random effect at the sample level, and which can also account for missing environmental covariates (Zurrell, Pollock, & Thuiller, ), accounted for 16.3% of the variance in the model.…”
Section: Discussionmentioning
confidence: 57%
“…The three sediment sites of highest estimated species richness CCP‐J, NOAH‐H (both impermeable sediments) and NOAH‐I (medium permeable) only had in common the furthest location from shore. Interestingly species richness of benthic infauna in these regions has also been described to be three times higher compared to sites in the coastal regions (Neumann et al ., ). Less frequent pulses of organic matter, for example through phytoplankton blooms, into the sediment in regions furthest offshore could explain the high estimated species richness in these regions.…”
Section: Discussionmentioning
confidence: 97%
“…() and Neumann et al . () analysing data from the same area found no relationship between diversity of demersal fish and epibenthos or macrofauna, even though patterns of community assemblages of the three components were largely similar. Reiss et al .…”
Section: Discussionmentioning
confidence: 86%
“…() and Neumann et al . () concluded that different processes may drive diversity versus community structure; indeed, at large spatial scales factors delineating regional species pools are likely to be important.…”
Section: Discussionmentioning
confidence: 99%